Бесы: роман / Ф. М. Достоевский - Достоевский Федор Михайлович (Репро, 1997)
Экземпляры: БС (20170719) / Инвентарный номер: РТШ48994 / Цена: 51.40 / Сис.шифр: Р1 / Авт.знак: Д 70 / ГРНТИ: 17 / ББК: 84(2=411.2)-4